Hybrid pelvic floor reconstruction using a vaginal flap with unilateral apical fixation in the management of post-hysterectomy prolapse: A retrospective study - Dmitry D. Shkarupa; Rustam A. Shakhaliev; Nikita D. Kubin; Andrei S. Shulgin; Zaynulabid I. Muldarov; Firdavskhuja P. Sultonov (Гинекология)
Aim. To evaluate the anatomical effectiveness and safety of hybrid pelvic floor reconstruction using a vaginal flap with unilateral apical fixation in women with post-hysterectomy prolapse.